2014
DOI: 10.12988/ams.2014.474551
|View full text |Cite
|
Sign up to set email alerts
|

Methane potentials from grape marc by a laboratory scale plant

Abstract: The choice of grape marc as biomass to produce energy has a double purpose. It provides a valid alternative to the handing over to distilleries, which represents a considerable cost for the community and also gives value to a form of agricultural-industrial waste. In this paper, the results of an experiment performed at ERSAF (Lombardy) in their laboratories in Mantova are assessed. A laboratory scale plant was used in order to evaluate the biogas and the methane produced by the anaerobic digestion (AD) of fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Grape marc as a potential source of biogas has been subject of research [41], attaining values of up to 28 Nm 3 t −1 . It produces a high yield of biogas on the first days (as could be expected by the high presence of sugars in the dry matter) which later decreases as sugars become depleted and the main source of biogas is the fibrous matter in grape waste.…”
Section: Wastes and By-products: Generation And Characteristicsmentioning
confidence: 99%
“…Grape marc as a potential source of biogas has been subject of research [41], attaining values of up to 28 Nm 3 t −1 . It produces a high yield of biogas on the first days (as could be expected by the high presence of sugars in the dry matter) which later decreases as sugars become depleted and the main source of biogas is the fibrous matter in grape waste.…”
Section: Wastes and By-products: Generation And Characteristicsmentioning
confidence: 99%
“…Anaerobic co‐digestion of different organic residues has been widely investigated with a view to enhancing the performance of anaerobic digestion regarding biogas production and total solids reduction . Usually, during a co‐digestion process one main basic feedstock (e.g., animal manure or sewage sludge) is mixed with a smaller amount of a second one (e.g., crop residues, silage, and food wastes) to feed the digester . Only a few studies have examined the co‐digestion of multiple feedstocks (Valenti et al ., unpublished) and demonstrated successful biogas production from multiple organic residues.…”
Section: State Of the Artmentioning
confidence: 99%
“…The average methane yields of the raw pomace, extracted pomace, and extracted pomace with aqueous supplement (E+S), adjusted per gram of volatile solids (VS), were 213.6 ± 10.15, 190.5 ± 18.27, and 205.9 ± 18.39 mL, respectively. These values are comparable to those from other studies of anaerobic digestion of RGP, in the range of 110−360 mL per gram of VS. [18][19][20][21][22]50 Methane production over time for each treatment is depicted in Figure 6. One-way ANOVA analysis of the terminal methane could not discern any significant differences (P = 0.17).…”
Section: Anthocyanin Extractionmentioning
confidence: 99%
“…In addition to anthocyanins, RGP also contains a small portion of nonfermented soluble sugars , and significant lignocellulose content (roughly half on a dry basis). Thus, it represents a potential feedstock for second-generation biofuel technologies such as anaerobic digestion. Several studies have found substantial biomethane yield from the anaerobic digestion of RGP, at values comparable to many other lignocellulosic agricultural residues …”
Section: Introductionmentioning
confidence: 99%